2019
DOI: 10.1007/s00125-019-4968-0
|View full text |Cite
|
Sign up to set email alerts
|

Racial/ethnic differences in the burden of type 2 diabetes over the life course: a focus on the USA and India

Abstract: Type 2 diabetes is a common disease worldwide, but its prevalence varies widely by geographical region and by race/ethnicity. This review summarises differences in the frequencies of type 2 diabetes according to race, ethnicity, socioeconomic position, area of residence and environmental toxins. Type 2 diabetes susceptibility often begins early in life, starting with genetic susceptibility at conception and continuing in later life, via in utero, childhood and adult exposures. Early-life factors may lead to ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 80 publications
1
45
0
Order By: Relevance
“…Recently Indian people with T2DM reported to have lower beta cell function compared with Europeans which is originates during intrauterine development, and not only diet; this fact support the ‘thrifty phenotype’ hypothesis. 60 Diet may also play a fundamental role in intergenerational vulnerability to T2DM. Maternal vitamin B12 deficiency and hyperhomocysteinemia are related to IR and adiposity in childhood.…”
Section: Discussionmentioning
confidence: 99%
“…Recently Indian people with T2DM reported to have lower beta cell function compared with Europeans which is originates during intrauterine development, and not only diet; this fact support the ‘thrifty phenotype’ hypothesis. 60 Diet may also play a fundamental role in intergenerational vulnerability to T2DM. Maternal vitamin B12 deficiency and hyperhomocysteinemia are related to IR and adiposity in childhood.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on mentioned associations did not include people from the Arab world. Genetic factors, and hence ethnicity play an important role in susceptibility to disease [ 34 , 35 ], In an earlier study, conducted in Jeddah, Saudi Arabia, [ 36 ], we reported an association between above than normal weight with dysglycemia, and hypertension, which was gender specific. Moreover, in another survey, conducted in the same city at a later date, high LDL-C was found to be associated with an increased probability of pre-diabetes (Al amri et al 2019), which points to the clustering of the three CVD risk factors, excess weight increased blood pressure and dysglycemia in the Saudi population, as noted in studies from other countries [ 12 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Type 2 diabetes is a common disease worldwide, but its prevalence varies widely across different ethnic groups. The prevalence of diabetes in the USA, according to self‐reported ethnicity and self‐reported physician‐diagnosed diabetes, ranges from 17.7% in white European individuals to 22.5% in Asians, 30.6% in Hispanics and Africans, and 45.2% in American Indians/Alaska Natives in adults ≥ 75 years of age [1]. This diversity is even evident in ethnic subgroups, where Indians have the highest risk of disease (38.8%) amongst Asians, and Mexicans have the highest prevalence (33.4%) amongst Hispanics [2].…”
Section: Introductionmentioning
confidence: 99%